CHARACTERISTICS OF COOPERATIVE AND NON-COOPERATIVE THEORIES: https://doi.org/10.5281/zenodo.15826218 - Bozorboyev , Diyorbek (International scientific and practical conference, 2025)
This study explores the features and distinctions of cooperative and non-cooperative game theories within the framework of institutional economics. While traditional neoclassical economics relies on differential calculus to analyze interactions among agents, institutional economics emphasizes the role of individual interactions and the institutions governing them. Game theory, initially developed by von Neumann and Morgenstern and later expanded by Nash, offers an effective tool for modeling such interactions. Cooperative games allow players to share information and form alliances, emphasizing collective strategies, while non-cooperative games focus on individual strategies without communication or agreements. Various equilibrium concepts — including dominant strategy equilibrium, Nash equilibrium, Stackelberg equilibrium, and Pareto optimality — illustrate different outcomes of strategic interaction. This analysis highlights the relevance of these equilibrium types in understanding conflict resolution and strategic decision-making processes in economics.